1998
DOI: 10.1103/physrevb.57.10936
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of theCu3O4plane of

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
2
4
1
Order By: Relevance
“…10 They are also consistent with earlier reports on the isostructural compound Ba 2 Cu 3 O 4 Cl 2 taken at a higher photon energy. 24,25 We confirm the observation that the spectral features about (π/2, π/2) have a remarkable resemblance to those in Sr…”
Section: Bi2sr2ercu2o8 and Bi2sr2dycu2o8supporting
confidence: 84%
See 1 more Smart Citation
“…10 They are also consistent with earlier reports on the isostructural compound Ba 2 Cu 3 O 4 Cl 2 taken at a higher photon energy. 24,25 We confirm the observation that the spectral features about (π/2, π/2) have a remarkable resemblance to those in Sr…”
Section: Bi2sr2ercu2o8 and Bi2sr2dycu2o8supporting
confidence: 84%
“…10 They are also consistent with earlier reports on the isostructural compound Ba 2 Cu 3 O 4 Cl 2 taken at a higher photon energy. 24,25 We confirm the observation that the spectral features about (π/2, π/2) have a remarkable resemblance to those in Sr 2 CuO 2 Cl 2 . It is astounding that the properties of the Zhang-Rice singlet seen in ACOC are almost undisturbed by the drastic change to the CuO 2 lattice in the case of Sr 2 Cu 3 O 4 Cl 2 .…”
Section: Bi2sr2ercu2o8 and Bi2sr2dycu2o8supporting
confidence: 83%
“…Cu 3 O 4 Cl 2 taken at a different photon energy [115,116]. Although, here we neither confirm nor deny their interpretation for the existence of two Zhang-Rice singlets on differing sublattices.…”
contrasting
confidence: 89%
“…The dispersion of a single hole in both antiferromagnetic and paramagnetic spin background was measured simultaneously in the same Cu 3 O 4 plane by ARPES experiments on 2342. [17][18][19] One of the most intriguing features in earlier studies is the weak ferromagnetic moment that appears below T N,I . 13,14,20,21 We have recently reported that anisotropic bond-dependent interactions such as pseudodipolar couplings can in fact explain such weak ferromagnetic moments.…”
Section: Introductionmentioning
confidence: 97%